Meanings of recovery and post-traumatic growth in people with lived experience of eating disorders: a qualitative study - Chiara Tosi; Davide Patanè; Ludovica Natali; Valentina Meregalli; Valentina Cardi (Journal of Eating Disorders)
Abstract Background Conceptualizations of recovery from an Eating Disorder (ED) have focused traditionally on symptom alleviation and restoration of physical health. In recent years, through patient involvement, this definition has been broadened to incorporate changes in psychological processes and overall wellbeing. This study used a qualitative approach to explore the meanings of recovery among people with lived experience of an ED. Areas of personal growth after the illness were explored, with reference to the theoretical framework of Post-Traumatic Growth (PTG). Methods Nineteen participants (mean age 24.37; range: 18–50), who self-identified as recovered from an ED (mean time since recovery = 33.68 months, standard deviation = 31.67 months; range = 5-130 months), completed a demographic questionnaire and were asked to discuss their experiences of recovery and areas of PTG in a structured interview. Reflexive Thematic Analysis (TA) was used to identify common themes and sub themes. Results Four overarching themes and 14 sub themes were identified. Recovery was defined as a non-linear process marked by changes in eating behaviours (e.g., greater flexibility), and more effective abilities to manage painful thoughts and emotions. Elements of PTG were included in the experience of recovery, particularly through a reconstituted, authentic and meaningful sense of self following the ED. Conclusions People with lived experience of an ED provided a broad definition of recovery, which encompassed symptom restoration, as well as significant changes in psychological processes and elements of PTG. These findings have the potential to inform the development or refinement of recovery-focused treatments.